Diagnostic Trials on Sorghum (Sorghum bicolor L. Moench) for Developing Site-specific Nutrient Management Practices in the Lowlands of Eastern Amhara, Ethiopia - Teshome, Habtemariam; Adissie, Samuel; Sisay, Kassa; Hailu, Tadesse (Department of Agronomy and Horticulture, IPB University, 2025)
Soil fertility heterogeneity significantly influences crop productivity and the effectiveness of nutrient management strategies. In Ethiopia, various types and sources of inorganic fertilizers are distributed to enhance crop production. Therefore, selecting appropriate fertilizers based on specific soil nutrient deficiencies is essential. A field experiment was conducted in Kobo using sorghum as the test crop to identify yield-limiting nutrients through crop response. The experiment employed a randomized complete block design with farmers’ fields serving as replications. Biological yield data were collected and analyzed using analysis of variance (ANOVA). When significant differences among treatments were detected, means were separated using the LSD test at P ≤ 0.05. Results showed that omitting nutrients from inorganic fertilizers, either individually or in combination, significantly reduced grain yield. The highest grain yield was achieved with the combined application of NPS (nitrogen, phosphorus, sulphur) fertilizer and farmyard manure (FYM). In contrast, the lowest yield occurred in the control treatment, where all nutrients were omitted. Biomass yield did not differ significantly between treatments across both years. The study indicates that applying farmyard manure in combination with inorganic fertilizers, such as NPS, NPSK (NPS + potassium), and NPSKZn (NPSK + Zinc), effectively meets the nutrient requirements of sorghum. Grain yield under nutrient omission treatments ranked as follows: NPS + FYM > NPS > NPSK > NPSKZn > NP > NS > PS > N > S > P. Among the nutrients tested, farmyard manure had the greatest impact on yield, followed by nitrogen, sulphur, and phosphorus fertilizers.